Features of the development of tuberculosis in children not vaccinated with BCG - O. M. Raznatovska; Yu. V. Myronchuk; O. O. Pushnova; L. I. Chernyshova; T. I. Shelestina; V. V. Bezdenezhnyi (Zaporožskij Medicinskij Žurnal)
According to the data from the State Institution "Public Health Center" of the Ministry of Healthcare of Ukraine in Zaporizhzhia region, starting from 2014, there is observed the increased rate of tuberculosis among children aged 0-17 years, in particular: in 2014 - 12.1 per 100 thousand of the population, in 2015 - 16.4 per 100 thousand of the population and in 2016 - 24.9 per 100 thousand of the population. At the same time, in 2016 this rate exceeded the national one by 2.3 times (10.5 if compared to 24.9). According to the Professor V.P. Kostorminova, the prophylactic activity of the BCG vaccine is 70-85% of the quality BCG vaccination and reduces the tuberculosis morbidity by 10 times and infectivity by 1.5-3 times.